The Sixteenth-Century Zinacantepec Census: Between Ethnohistory and Historical Demography. - Megged, Amos (Ethnohistory, 2020)
While earlier census studies yielded population data mainly for the Tepetlaoztoc and Morelos regions of central Mexico during the 1530s and 1540s, this ethnohistoric study, based on a newly discovered manuscript, sheds light on household types and population density in the town of Zinacantepec by 1574. By comparing population figures, household types, and migration patterns, this article reconsiders how Aztec invasion, and thereafter the Spanish conquest, affected population movements and stability in the Valley of Toluca, a former Aztec stronghold in central Mexico. Furthermore, the nature of Toluca Valley habitats may prompt us to rethink about how we interpret the nature of indigenous demographic layouts before and after the Spanish conquest, whether its features be urban or rural.